2013
DOI: 10.1007/7854_2013_256
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Huntington’s Disease

Abstract: In this review, we explore the similarities and differences in the behavioural neurobiology found in the mouse models of Huntington's disease (HD) and the human disease state. The review is organised with a comparative focus on the functional domains of motor control, cognition and behavioural disturbance (akin to psychiatric disturbance in people) and how our knowledge of the underlying physiological changes that are manifest in the HD mouse lines correspond to those seen in the HD clinical population. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 252 publications
0
18
0
Order By: Relevance
“…However, these same synapses must be able to reverse this form of plasticity (ie, induction of LTD) to allow extinction or “forgetting” processes in response to new behavioral situations. Earlier genetic and pharmacological studies showed involvement of various striatal signaling molecules and circuits in behavioral flexibility …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these same synapses must be able to reverse this form of plasticity (ie, induction of LTD) to allow extinction or “forgetting” processes in response to new behavioral situations. Earlier genetic and pharmacological studies showed involvement of various striatal signaling molecules and circuits in behavioral flexibility …”
Section: Discussionmentioning
confidence: 99%
“…Earlier genetic and pharmacological studies showed involvement of various striatal signaling molecules and circuits in behavioral flexibility. 162,163 In this review, we pointed out that the emergence of abnormal activity pattern in striatal cholinergic interneurons that accompanied the dysfunction of striatal ACh signaling in BG disorders might contribute to pathological cortico-striatal synaptic plasticity. This abnormal cortico-striatal synaptic plasticity probably underlies some of the clinical disturbances in learning and switching behaviors seen in patients with BG disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A number of HD mouse models have been created over the years since the discovery of the causal mutation in the HTT gene. These models have been reviewed in detail elsewhere (Brooks and Dunnett, 2013;Pouladi et al, 2013), and here we will only highlight the ones that are most frequently used for the study of HD-related circuit defects ( Table 1). They can be divided into truncated and full-length models, the latter including transgenic and knock-in lines.…”
Section: Genetic Mouse Models Of Hdmentioning
confidence: 99%
“…For example, Huntington’s disease takes many years to evolve in humans, and to accelerate the process in mice, transgenics have been constructed that express much longer polyglutamine expansions than those appearing in nature. Perhaps as a result, none of the many types of nominally Huntington disease mice thus far developed faithfully replicate both the typical disease course and neuropathology of the disease in humans (Brooks and Dunnett, 2015; Howland and Munoz-Sanjuan, 2014; Menalled and Brunner, 2014). As such, whether cell therapeutic strategies modeled in these mice will prove as efficacious in HD patients remains an uncomfortable unknown.…”
Section: Hype: Limits To Therapeutic Advancementioning
confidence: 99%